Analysis Of Full Bridge Boost Converter For Wide Input Voltage Range (International Journal of Engineering and Computer Science, 2013)
A family of isolated dc/dc converters for wide input-voltage range is proposed in this paper, and the full-bridge(FB) boost converter, being one of the typical topologies, is analyzed. Due to the existence of the resonant inductor (including the leakage inductor), the FB-boost converter can only adopt the two-edge-modulation (TEM) scheme with the FB cell being leading-edge modulated and the boost cell being trailing-edge modulated to minimize the inductor current ripple over the input-voltage range, and a phase-shift-control-schemebased TEM is proposed which realizes phase-shifted control for the FB cell to achieve zero-voltage switching. In order to improve the reliability and efficiency of the FB-boost converter, a three-mode dual-frequency control scheme is proposed, in which the FB-boost converter operates in boost, FB-boost and FB modes in low, medium and high input voltage regions, respectively, and for which the expression of the inductor current ripple is derived in this paper. A 250–500 V input, 360 V output, and 6 kW rated power prototype is fabricated to verify the effectiveness of the design and control method.